2014
DOI: 10.1002/14651858.cd005999.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cyst aspiration prior to in vitro fertilization treatment for subfertility

Abstract: Background Ten per cent to 15% of couples have difficulty in conceiving. A proportion of these couples will ultimately require assisted reproduction. Prior to controlled ovarian hyperstimulation (COH) a baseline ultrasound is performed to detect the presence of ovarian cysts. Previous research has suggested that there is a relationship between the presence of an ovarian cyst prior to COH and poor outcome of in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Ovarian cyst aspiration prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…A total of 17-44% of infertile patients with endometriosis are diagnosed with ovarian endometrioma (Vercellini et al, 2003). Surgical excision, cyst aspiration, hormonal treatment, ethanol injection as well as leaving the cysts in situ are management options of endometrioma in infertile women (Beretta et al, 1998;Brown and Farquhar, 2014;McDonnell et al, 2014;Garcia-Tejedor et al, 2015). Yet, optimal management is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 17-44% of infertile patients with endometriosis are diagnosed with ovarian endometrioma (Vercellini et al, 2003). Surgical excision, cyst aspiration, hormonal treatment, ethanol injection as well as leaving the cysts in situ are management options of endometrioma in infertile women (Beretta et al, 1998;Brown and Farquhar, 2014;McDonnell et al, 2014;Garcia-Tejedor et al, 2015). Yet, optimal management is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that there is insufficient evidence to determine whether drainage of functional ovarian cysts prior to controlled ovarian hyperstimulation (COH) influences clinical pregnancy rate, live birth rate, the number of follicles recruited, or oocytes collected in women with an ovarian cyst. The conclusions of this review do not provide supportive evidence for this approach, especially in view of the requirement for anesthesia, extra cost, psychological distress and the risk of surgical complications (81).…”
Section: Risk Of Conservative Management Of Endometrioma Before Ivfmentioning
confidence: 82%
“…The effect of functional ovarian cysts on clinical outcomes after 258 GnRH-a usage is controversial. There is insufficient evidence to determine whether drainage of 259 functional ovarian cysts prior to controlled ovarian hyperstimulation negatively influenced live 260 birth rate, clinical pregnancy rate, number of follicles recruited, or oocytes collected in women 261 with a functional ovarian cyst [McDonnell, Marjoribanks & Hart, 2014]. In this research, the 262 formation rate of functional ovarian cysts was much lower than that of nonfunctional cysts.…”
mentioning
confidence: 74%
“…The pathophysiological mechanism of cyst formation is unknown so 235 far. However, possible mechanisms have been published [Feldberg et al, 1989; Pereira et al, 236 2016;McDonnell et al, 2014]. It is easy for ovarian cysts to form when initiated at the follicular 237 phase, especially in women with higher basal FSH levels during their menstrual cycle.…”
mentioning
confidence: 99%